Future Developments in the Treatment of AL Amyloidosis - Foteini Theodorakakou; Despina Fotiou; Meletios A. Dimopoulos; Efstathios Kastritis (Hemato, 2022)
The treatment of AL amyloidosis has evolved, and outcomes have improved, but primarily for patients with low or intermediate-risk disease. Recent advances have been limited to improvements in anti-clonal therapies, which, alone, cannot change the poor prognosis of patients with high-risk disease. Thus, new strategies are needed that combine different approaches to the treatment of the disease. Targeted therapies against plasma/B-cell clones that avoid chemotherapy or potentially cardiotoxic drugs may improve the depth of hematologic responses and reduce complications. Amyloid fibril and light-chain oligomer targeting may reduce direct toxicity and enhance tissue clearance. Future combinations should be tailored to clone characteristics and specific amyloid properties, but early identification of those at high risk to develop AL amyloidosis will also be integrated into management algorithms.